Unveiling the Benefits: The Crucial Role of Navaneeta in Chaturtha Masa of Pregnancy (AYUSHDHARA, 2024)
Ayurveda gives more significance to Ahara for a healthy life. The care taken by mother and care to be given by the Ayurveda with timely observation is Garbhini Paricharya. According to Ayurvedic perspective Garbhini Paricharya refers to antenatal care with recommendation of Ahara, Vihara and psychological behaviour. Acharyas have described monthly dietary regimen to meet increase calories requirements of the pregnant women. Among that for fourth month Navaneeta is advised as it is basically Snigdha, Sangrahi, having Sheeta Guna in turn helps in preventing Garbhapaata. Consuming Navaneeta in a genuine quantity is the foremost thing. Proper adaptation of Garbhini Paricharya, ensures not only healthy progeny but also normal healthy delivery and helpful to the mother in postnatal period. Materials and Methods: Samhitas, Nighantus, text books of Prasootitantra and Streeroga, Bhaisajyakalpana, publications and relevant, authenticated online websites are referred for the collection of information. Result and Discussion: Navaneetha is having Sangrahi, Sheeta, Snigdha Guna in dominance. Based on this, relation is established between properties of Navaneeta (Ayurveda view), butter (modern view) and fetus development condition. Thus an attempt is made to give clarification on administration of Navaneeta especially in fourth month and also on what basis Acharyas suggested Navaneeta at this particular period of time.